Carrie Mae Weems - "un gran giro de lo posible" - Dyangani Ose, Elvira 1974-; Dressler, Iris 1966- (Fundación MAPFRE, 2022)
"One of the most influential American artists working today, Carrie Mae Weems has investigated narratives around family, race, gender, sexism, class and the consequences of power for more than 40 years. Her complex oeuvre-always ahead of its time, and profoundly formative for younger generations of artists-has employed photography (for which she is best known), fabric, text, audio, digital images, installation and video. Writing in the New York Times, Holland Cotter succinctly described Weems as "a superb image maker and a moral force, focused and irrepressible." This volume, spanning four decades of work, is the most thorough survey yet published. It includes Weems' earliest series, such as Family Pictures and Stories, for which she photographed her relatives and close friends; the legendary Kitchen Table Series, in which she posed in a domestic setting; and other critically acclaimed works and series such as Ain't Jokin', Colored People, From Here I Saw What Happened and I Cried, Not Manet's Type, The Jefferson Suite, Monuments, Roaming, Museums, Constructing History (A Class Ponders the Future), Slow Fade to Black and the Obama Project, among many others. Contextualizing these pieces are essays by LaCharles Ward and Fred Moten and a chronology by Raul Muñoz. The book also includes a visual essay by Weems that presents a personal selection of her own works from the artist's perspective. The accompanying exhibition is organized by Fundación MAPFRE in collaboration with Fundación Foto Colectania, Barcelona and Württembergischer Kunstverein, Stuttgart, where the exhibition Carrie Mae Weems. The Evidence Of Things Not Seen took place from April 2 through August 21, 2022"--
"This publication, edited by Fundación MAPFRE in Spanish and Catalan and co-published by D.A.P./Distributed Art Publishers in English, accompanies Carrie Mae Weems multisite project at the following locations: The Evidence of Things Not Seen, Württembergischer Kunstverein Stuttgart (WKV), Stuttgart, April 2-August 21, 2022, [and] A Great Turn in the Possible, KBr Fundación MAPFRE, Barcelona, Fundación Foto Colectania, Barcelona, October 5, 2022-January 15, 2023."--Colophon
Keywords: Weems, Carrie Mae -- 1953-; Ausstellungskatalog -- Württembergischer Kunstverein -- 02.04.2022-21.08.2022 -- Stuttgart; Ausstellungskatalog -- Centro de Fotografía KBr -- 05.10.2022-15.01.2023 -- Barcelona; Bildband